EMIC Waves Converted From Equatorial Noise Due to M/Q = 2 Ions in the Plasmasphere: Observations From Van Allen Probes and Arase. Issue 11 (7th June 2019) - Miyoshi, Y.; Matsuda, S.; Kurita, S.; Nomura, K.; Keika, K.; Shoji, M.; Kitamura, N.; Kasahara, Y.; Matsuoka, A.; Shinohara, I.; Shiokawa, K.; Machida, S.; et al.
Abstract: Equatorial noise (EN) emissions are observed inside and outside the plasmapause. EN emissions are referred to as magnetosonic mode waves. Using data from Van Allen Probes and Arase, we found conversion from EN emissions to electromagnetic ion cyclotron (EMIC) waves in the plasmasphere and in the topside ionosphere. A low‐frequency part of EN emissions becomes EMIC waves through branch splitting of EN emissions, and the mode conversion from EN to EMIC waves occurs around the frequency of M / Q = 2 (deuteron and/or alpha particles) cyclotron frequency. These processes result in plasmaspheric EMIC waves. We investigated the ion composition ratio by characteristic frequencies of EN emissions and EMIC waves and obtained ion composition ratios. We found that the maximum composition ratio of M / Q = 2 ions is ~10% below 3, 000 km. The quantitative estimation of the ion composition will contribute to improving the plasma model of the deep plasmasphere and the topside ionosphere. Plain Language Summary: Equatorial noise (EN) emissions are whistler mode waves. Using Van Allen Probe and Arase (ERG) plasma wave data, we found that EN emissions propagate toward the Earth and are converted to electromagnetic ion cyclotron (EMIC) waves in the deep plasmasphere and the topside ionosphere. We suggest that minor ions with a mass per charge ( M / Q ) = 2, that is, deuteron or alpha particles, play an important role in this process. The processes reported here are a new generation process of plasmaspheric EMIC waves. Moreover, we determined the ion composition ratio using characteristics of wave dispersion. We derived the altitude profile of the ion composition ratio and identified the maximum ratio of M / Q = 2 ions of about 10% in the deep plasmasphere. Key Points: The first measurements of the conversion from equatorial noise to EMIC waves are presented Existence of M / Q = 2 ions (deuteron or alpha particle) in the deep plasmasphere is essential to cause the conversion The ion composition ratio is quantitatively estimated in the deep plasmasphere using characteristics of the wave dispersion